PENGARUH KEPEMILIKAN INSTITUSIONAL DAN FREE CASH FLOW TERHADAP KEBIJAKAN HUTANG - Safitri, Indah; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to test the influence of institutional ownership and free cash flow to the debt policy in the manufacturing companiesin the consumer goods sector which are listed in the Indonesia Stock Exchange in 2010-2013 periods. The hypotheses in this research i.e. : (1) the institutional ownership has negative influence the to the debt policy. (2) Free Cash Flow has positive influence to the debt policy. The research method which has been done is quantitative method which isdone by using the multiple linear regressionsas the analysis technique. The assumption tests consist of normality test, the multicolonearity test, the autocorrelation test, and the heteroscedasticity. The result of the research shows that: (1) the institutional ownership does not have any influence to the debt policy. Because the institutional ownership is applied as the supervisor to the management performance and the management is considered as the partywhich has bettercomprehension about the need of funding within the company sothe institutional ownership acts as the precaution to the waste of funds which has been done by the management; (2) free cash flow has significant influence to the coefficient ofnegativeÎ². It shows that highfree cash flow will make the company reduce their decision in taking the debt, because the free cash flow can be used to finance the operational of the company by allocating most of the profit of retained earnings without seeking additional external funds from the debt.Keywords: Institutional Ownership, Free Cash Flow, Debt Policy, Agency Theory